Phonetic Effects in the Perception of VOT in a Prevoicing Language - Viktor Kharlamov (Brain Sciences, 2022)
Previous production studies have reported differential amounts of closure voicing in plosives depending on the location of the oral constriction (anterior vs. posterior), vocalic context (high vs. low vowels), and speaker sex. Such differences have been attributed to the aerodynamic factors related to the configuration of the cavity behind the oral constriction, with certain articulations and physiological characteristics of the speaker facilitating vocal fold vibration during closure. The current study used perceptual identification tasks to examine whether similar effects of consonantal posteriority, adjacent vowel height, and speaker sex exist in the perception of voicing. The language of investigation was Russian, a prevoicing language that uses negative VOT to signal the voicing contrast in plosives. The study used both original and resynthesized tokens for speaker sex, which allowed it to focus on the role of differences in VOT specifically. Results indicated that listeners’ judgments were significantly affected by consonantal place of articulation, with listeners accepting less voicing in velar plosives. Speaker sex showed only a marginally significant difference in the expected direction, and vowel height had no effect on perceptual responses. These findings suggest that certain phonetic factors can affect both the initial production and subsequent perception of closure voicing.